The Behavior Prevention Modification of Non-Communicable Diseases During the COVID-19 Pandemic Using Android-Based Telenursing Application "SI-TELUR PETIS" - Mei Rianita Elfrida Sinaga; Indrayanti Indrayanti; Muhammad Irfan (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Pandemic Covid-19 pandemic became a global health threat that impacts the health sector, including non-communicable diseases. Innovation efforts of nursing non-pharmacological is behavior modification using android-based telenursing application. This study aimed to determine the effect of android-based telenursing application "SI-TELUR PETIS" as behavior prevention modification of non-communicable diseases during the COVID-19 pandemic. Design: This study is a quantitative study using the quasi-experimental study with pre and post-test with control group design. Methods: The sample of this study amounted to 60 respondents with 30 respondents in the intervention group and 30 respondents in the control group were selected using purposive sampling. Data were collected from May to August 2021. The application has been validated by adopting the ISO 9126 about the quality of the software that has the six aspects of assessment. Mann Whitney U and Wilcoxon tests were used for data analyses. Results: Android-based telenursing application "SI-TELUR PETIS" has a significant effect on the change in the behavior prevention modification of non-communicable diseases (DM and Hypertension) (p<.05). Conclusions: Overall the application is easy to understand the purpose and usefulness coupled with the explanation of the groove of the use of the application. Android-based telenursing application "SI-TELUR PETIS" has a significant effect on behavior prevention modification of non-communicable diseases (DM and Hypertension) through the features of the daily note, namely diet, and physical activity